Comparison of minimally invasive and open TLIF outcomes with more than seven years of follow-up - Jae-Young Hong; Won Seok Kim; Jiwon Park; Chi Heon Kim; Hae-Dong Jang (North American Spine Society Journal, 2022)
Background: Few studies directly comparing minimally invasive (MI) transforaminal lumbar interbody fusion (TLIF) and open TLIF offering long-term follow-up data have been performed to date. Therefore, we sought to compare mid- to long-term outcomes between these two surgical approaches. Methods: This was a retrospective data analysis of two surgical groups. We analyzed the details of 97 patients with degenerative lumbar disease who were treated with MI TLIF (n = 55) or open TLIF (n = 42) between 2011–2014 and had at least seven years of follow-up data available. Peri- and postoperative outcomes were compared. To evaluate rates of adjacent segment disease (ASD) and revisions, frequencies of radiologic, symptomatic, and operative ASD were analyzed accordingly. Results: In terms of clinical outcome, the Oswestry Disability Index and visual analog scale scores were significantly reduced, with no difference between the groups. However, data for several peri- and postoperative outcomes, including perioperative blood loss, ambulation day, hospital stay, and operation time, varied in a manner favoring the MI TLIF group (P < 0.05). Rates of radiologic ASD and symptomatic ASD were significantly higher in the open TLIF group beginning at five years of follow-up (P < 0.05), while the rate of operative ASD and the revision rate were similar between the groups. Other long-term outcomes, including fusion rate and complications, remained similar between the two groups at 7 years. Conclusion: Patients undergoing MI TLIF showed favorable immediate postoperative outcomes and less radiographic ASD. However, the rates of fusion and operative ASD remained similar between the two groups after 7 years of follow-up.